2000
DOI: 10.1200/jco.2000.18.6.1173
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Dose-Intensive Paclitaxel, Ifosfamide, Carboplatin, and Etoposide Salvage Therapy for Germ Cell Tumor Patients

Abstract: Dose-intense therapy with sequential, accelerated chemotherapy of paclitaxel/ifosfamide and carboplatin/etoposide administered with PBSC support was relatively well tolerated. The durable complete response proportion was substantial in patients with unfavorable prognostic features for achieving durable complete response to conventional-dose salvage programs. Optimal dosing of carboplatin in the high-dose setting warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
104
0
8

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(115 citation statements)
references
References 19 publications
3
104
0
8
Order By: Relevance
“…[56][57][58][59][60][61][62][63][64][65][66][67][68][69] Paclitaxel was shown to Chemo., chemotherapy; CR, complete response; NED, no evidence of disease; VeIP, vinblastine, ifosfamide, cisplatin; VIP, etoposide (VP-16), ifosfamide, cisplatin. be effective for previously treated testicular cancer because of its unique mechanism of antitumor activity and the premature stabilization of the microtubules assembly, which is different from that of DNAdamaging agents such as cisplatin and ifosfamide.…”
Section: Poor-prognosis Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…[56][57][58][59][60][61][62][63][64][65][66][67][68][69] Paclitaxel was shown to Chemo., chemotherapy; CR, complete response; NED, no evidence of disease; VeIP, vinblastine, ifosfamide, cisplatin; VIP, etoposide (VP-16), ifosfamide, cisplatin. be effective for previously treated testicular cancer because of its unique mechanism of antitumor activity and the premature stabilization of the microtubules assembly, which is different from that of DNAdamaging agents such as cisplatin and ifosfamide.…”
Section: Poor-prognosis Diseasementioning
confidence: 99%
“…The first trial of paclitaxel in pretreated germ cell tumors was undertaken by Motzer et al 56 The effective rate of paclitaxel in the salvage treatment of refractory testicular cancer ranged from 11 to 26% (Table 5). [56][57][58][59][60][61][62][63][64][65][66][67][68][69] More recently, high effective rates (68% and 80%) of a combination chemotherapy with paclitaxel, ifosfamide and cisplatin (TIP) in the treatment of refractory disease were reported by Beyer et al and Motzer et al 60,61 The results reported by Motzer et al showed a high response rate to the TIP regimen in patients with relapsed testicular cancer after conventional dose first-line chemotherapy. 61 Motzer and associates also reported the result of dose-intensive salvage therapy with paclitaxel, ifosfamide, carboplatin and etoposide (PICP) for cisplatin-resistant germ cell tumor patients with unfavorable prognostic features, achieving a 57% CR rate.…”
Section: Poor-prognosis Diseasementioning
confidence: 99%
See 3 more Smart Citations